ChemInform Abstract: New Sesquiterpenoids Isolated from Atractylodes lancea Fermented by Marine Fungus. Issue 29 (July 2015) - Kamauchi, Hitoshi; Kinoshita, Kaoru; Takatori, Kazuhiko; Sugita, Takashi; Takahashi, Kunio; Koyama, Kiyotaka
Abstract From the fermented rhizomes of A.